Structure and tectonic evolution of the southwestern Trinidad dome, Escambray complex, Central Cuba: Insights into deformation in an accretionary wedge - Despaigne-Díaz, A.; García Casco, A.; Cáceres Govea, D.; Wilde, Simon; Millán Trujillo, G. (Elsevier BV, 2017)
© 2017 Elsevier B.V. The Trinidad dome, Escambray complex, Cuba, forms part of an accretionary wedge built during intra-oceanic subduction in the Caribbean from the Late Cretaceous to Cenozoic. The structure reflects syn-subduction exhumation during thickening of the wedge, followed by extension. Field mapping, metamorphic and structural analysis constrain the tectonic evolution into five stages. Three ductile deformation events (D 1 , D 2 and D 3 ) are related to metamorphism in a compressional setting and formation of several nappes. D 1 subduction fabrics are only preserved as relict S 1 foliation and rootless isoclinal folds strongly overprinted by the main S 2 foliation. The S 2 foliation is parallel to sheared serpentinised lenses that define tectonic contacts, suggesting thrust stacks and underthrusting at mantle depths. Thrusting caused an inverted metamorphic structure with higher-grade on top of lower-grade nappes. Exhumation started during D 2 when the units were incorporated into the growing accretionary wedge along NNE-directed thrust faults and was accompanied by substantial decompression and cooling. Folding and thrusting continued during D 3 and marks the transition from ductile to brittle-ductile conditions at shallower crustal levels. The D 4–5 events are related to extension and contributed to the final exhumation (likely as a core complex). D 4 is associated with a regional spaced S 4 cleavage, late open folds, and numerous extension veins , whereas D 5 is recorded by normal and strike-slip faults affecting all nappes. The P-t path shows rapid exhumation during D 2 and slower rates during D 3 when the units were progressively incorporated into the accretionary prism. The domal shape formed in response to tectonic denudation assisted by normal faulting and erosion at the surface during the final stages of structural development. These results support tectonic models of SW subduction of the Proto-Caribbean crust under the Caribbean plate during the latest Cretaceous and provide insights into the tectonic evolution of accretionary wedges in an intra-arc setting.